Formal Education in Indonesia and Egypt: Comparison of Challenges in Teaching English on Secondary Level - Dewi Nurpitriyani; Ibrahim El Sayed Abdel Moneim Attia Salama; Ratu Erlinda Kurniatillah; Nida Husna; Itje Chodijah; Didin Nuruddin Hidayat (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2022)
This research aims to compare the challenges in teaching English between Indonesia and Egypt. This study is restricted to the secondary level for formal education in both countries. The study is also investigated the teacher’s problems for formal education in Indonesia and Egypt and what are the challenges that the English teachers may face while teaching in both countries. The research used the comparative method of studying to evaluate and compare the challenges and causes for common problems in formal education in teaching English in both countries. Data were collected in two different ways; the questionnaire and interview. There were 30 English teachers as respondents in this research who teach in several cities in Indonesia and Egypt. The result of the study revealed that several similar challenges found in English teaching both in Indonesia and Egypt, such as students‘ lack participations, numbers of students in a classroom, teachers‘ competency in the curriculum implementation, and teachers‘ management skill. This study uncovered ways to overcome these challenges such as joining seminars to enlighten teachers‘ competences, dividing students into smaller groups, asking them one by one to share their thought, applying the classroom in the beginning of the class, and giving remedials to the ones who need extra attention.